The Palgrave Handbook of Media Misinformation
XLIV, 386 p. 29 illus., 25 illus. in color.
Keywords: The Palgrave Handbook of Media Misinformation provides a comprehensive and cutting-edge resource on the critical debates surrounding fake news and misinformation online. Spanning all continents and linking academic, journalistic, and educational communities, this collection offers authoritative coverage of conspiracy theories, the post-Trump and Brexit landscape, and the role of big tech in threats to democracy and free speech. The collection moves through a diagnosis of misinformation and its impacts on democracy and civic societies, the 'mainstreaming' of conspiracy theory, the impacts of misinformation on health and science, and the increasing significance of data visualization. Following these diagnoses, the handbook moves to responses from two communities of practice – the world of journalism and the field of media literacy. .